Comparative effect of a new mouthrinse containing chlorhexidine, triclosan and zinc on volatile sulphur compounds: a randomized, crossover, double‐blind study. Issue 3 (26th February 2015) - Mendes, L; Coimbra, J; Pereira, AL; Resende, M; Pinto, MG
Abstract: Aim: The aims of this study were to compare the volatile sulphur compounds (VSC)‐reducing effect of two commercial mouthrinses using a morning bad breath model and to assess the role of mechanical plaque control (MPC) when performed previously to mouthrinse use. Patients and methods: Eleven volunteers with good oral health were enrolled in a double‐blind, randomized, six‐step crossover design study with a 7‐day washout period. Two commercial mouthrinses were tested using a saline solution (NaCl 0.9%) as a negative control: one mouthrinse contained 0.05% chlorhexidine, 0.05% cetylpyridinium chloride and 0.14% zinc lactate (CHX‐CPC‐Zn), while the other contained 0.05% chlorhexidine, 0.15% triclosan and 0.18% zinc pidolate (CHX‐triclosan‐Zn). A portable sulphide monitor (Halimeter ® ) was used for VSC quantification. Measurements were made at baseline, and 1, 3 and 5 h after rinsing. Significant differences were detected by analysis of variance. Results: No significant differences between groups were detected at baseline. We were unable to demonstrate a significant influence of mechanical plaque control on the reduction of VSC levels when performed before mouthrinse use ( P  = 0.631). Both mouthrinses effectively lowered VSC levels in all test intervals ( P  < 0.05). No statistically significant differences were found between mouthrinses in any of the test intervals ( P  = 0.629, 0.069 and 0.598 at 1, 3 and 5 h). Conclusion: This study demonstrated that CHX‐CPC‐Zn and CHX‐triclosan‐Zn have significant and similar effects in reducing VSC levels, which persist for at least 5 h. Such effects were independent of previous MPC, which failed to improve on the results of mouthrinse use alone.